Reduction of disc brake squeal noise using constrained layer dampers (CLD) - Arvin Rao Subramaniam, author 611820; Abd. Rahim Abu Bakar, supervisor 303449; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2017